Forum Gumeulis: Upaya Peningkatan Kompetensi Guru dalam Menulis Karya Ilmiah di Kota Tasikmalaya - Caswita (Andragogi: Jurnal Diklat Teknis Pendidikan dan Keagamaan, 2020)
[FORUM GUMEULIS: EFFORTS TO IMPROVE TEACHER COMPETENCE IN WRITING SCIENTIFIC PAPERS IN TASIKMALAYA CITY]. The purpose of this study is to describe efforts to improve teacher competency in writing scientific papers through the activities of the Gumeulis forum in the City of Tasikmalaya, through training, guidance, mentoring and hands-on practice. The research method used is qualitative research with a type of case study. Data collection techniques through interviews, observation, and study of documentation. The results showed: (1) improvement of teacher competency in the city of Tasikmalaya in making the scientific paper more effectively carried out through teacher writing forums. (2) the development of teacher professional competence in making scientific papers through the Gumeulis forum activities shows an increase in teacher competency. (3) through the Gumeulis forum, there is mutual interaction together to learn to make Eastern Indonesia. (4), the Gumeulis Forum can create a conducive academic climate in improving teacher competency in creating scientific papers. The conclusion of the research shows that by learning together in the community will be able to improve the competence of teachers in writing scientific papers. This is because among members can discuss and learn together. Under the guidance of senior teachers in the community.